Portrait Of The Japanese Colonial Period In The Wayang Kamasan Illustration Of ‘Lintang Perau Pegat’ At The Klungkung Royal Palace - I Wayan Agus Eka Cahyadi (Institut Seni Indonesia Denpasar, 2021)
The Wayang Kamasan illustrations at the Klungkung Royal Palace store traces of the history of Bali during the Japanese colonial period. This research analyzed one located in the Bale Kambang pavilion with the ‘Lintang Perau Pegat’ scene to discern representation in that era. An art historical method was used drawing from field observation and literature resources with an iconography and iconology analysis approach of Erwin Panofsky. Findings from a pre-iconography phase showed that this illustration presents a scene about the splitting of a Japan-flagged ship by a large fish. An iconographic analysis was about themes and concepts regarding belief in the strength of nature (gods), which can influence human life and undermine the glory of human beings. Given the psychological atmosphere during the Japanese colonial period, hence, this illustration is the crystallization of a symbol from an attitude of resistance amidst helplessness towards a ruler (the Japanese occupation government), and hopes for the presence of the power of the gods to help eliminate oppression and misery that occurred during that era in Bali.